MUSIK SEBAGAI SARANA AKTUALISASI MISI PENGAJARAN DAN PELAYANAN DALAM GEREJA - Yusni Stasia Siramba’; Jeni Pasalli, Rajin Namba, Meriani Rerung Datte (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
Music plays a significant role in worship and church activities, and this research focuses on how music can be used as a tool to support the mission of teaching and service in the church. Therefore, this study aims to investigate how music can become an effective means of actualizing the mission of teaching and service within the church environment. The research employs a qualitative approach, collecting data through closed observations and document analysis. This study will involve the analysis of church music texts used in the context of teaching and service. The results of this research will reveal various ways in which music is used in the church to support the teaching of religious values, character formation, and community service. Music can serve as a means that enables deep spiritual experiences for the church congregation, aiding them in better understanding and internalizing religious teachings. Furthermore, this research will identify challenges and opportunities in using music as a tool for the church's mission and provide recommendations for enhancing the use of music within the church context. This study is expected to provide a deeper understanding of the role of music in the church as a means of actualizing the mission of teaching and service. The results of this research are also expected to offer practical guidance for churches in effectively utilizing music to achieve their mission goals